Why Um Helps Auditory Word Recognition: The Temporal Delay Hypothesis - Corley, Martin; Hartsuiker, Robert J. (PLOS ONE, 2011)
Several studies suggest that speech understanding can sometimes benefit from the presence of filled pauses (uh, um, and the like), and that words following such filled pauses are recognised more quickly. Three experiments examined whether this is because filled pauses serve to delay the onset of upcoming words and these delays facilitate auditory word recognition, or whether the fillers themselves serve to signal upcoming delays in a way which informs listeners' reactions. Participants viewed pairs of images on a computer screen, and followed recorded instructions to press buttons corresponding to either an easy (unmanipulated, with a high-frequency name) or a difficult (visually blurred, low-frequency) image. In all three experiments, participants were faster to respond to easy images. In 50% of trials in each experiment, the name of the image was directly preceded by a delay; in the remaining trials an equivalent delay was included earlier in the instruction. Participants were quicker to respond when a name was directly preceded by a delay, regardless of whether this delay was filled with a spoken um, was silent, or contained an artificial tone. This effect did not interact with the effect of image difficulty, nor did it change over the course of each experiment. Taken together, our consistent finding that delays of any kind help word recognition indicates that natural delays such as fillers need not be seen as ‘signals’ to explain the benefits they have to listeners' ability to recognise and respond to the words which follow them.